Impact of the first-line treatment shift from dihydroartemisinin/piperaquine to artesunate/mefloquine on Plasmodium vivax drug susceptibility in Cambodia. (24th March 2020) - Roesch, Camille; Mairet-Khedim, Mélissa; Kim, Saorin; Lek, Dysoley; Popovici, Jean; Witkowski, Benoit
Abstract: Background: Cambodia is the epicentre of the emergence of Plasmodium falciparum drug resistance. Much less is known regarding the drug susceptibility of the co-endemic Plasmodium vivax . Only in vitro drug assays can determine the parasite's intrinsic susceptibility, but these are challenging to implement for P. vivax and rarely performed. Objectives: To evaluate the evolution of Cambodian P. vivax susceptibility to antimalarial drugs and determine their association with putative markers of drug resistance. Methods: In vitro response to three drugs used in the past decade in Cambodia was measured for 52 clinical isolates from Eastern Cambodia collected between 2015 and 2018 and the sequence and copy number variation of their pvmdr1 and pvcrt genes were analysed. pvmdr1 polymorphism was also determined for an additional 250 isolates collected in Eastern Cambodia between 2014 and 2019. Results: Among the 52 cryopreserved isolates tested, all were susceptible to the three drugs, with overall median IC50 s of 16.1 nM (IQR 11.4–22.3) chloroquine, 3.4 nM (IQR 2.1–5.0) mefloquine and 4.6 nM (IQR 2.7–7.0) piperaquine. A significant increase in chloroquine and piperaquine susceptibility was observed between 2015 and 2018, unrelated to polymorphisms in pvcrt and pvmdr1 . Susceptibility to mefloquine was significantly lower in parasites with a single mutation in pvmdr1 compared with isolates with multiple mutations. The proportion of parasites with this single mutation genotype increased between 2014 and 2019. Conclusions: P. vivax with decreased susceptibility to mefloquine is associated with the introduction of mefloquine-based treatment during 2017–18.